Economic valuation of ecotourism site conservation the case of Nadsadjan Falls in Brgy, Passi, Igbaras, Iloilo. - Jugado, Evelyn E
This study focuses on the economic valuation of Nasadjan Falls aimed at determining its recreational and conservation values. Contingent valuation method (CVM) was used in determining the conservation value,while estimates on travel costs were used in determining the recreational value of Nasadjan Falls. The dichotomous choice format was used in the elicitation of responses. The socio-economic characteristics of the respondents were identified inorder to determine whether these affect the willingness to pay for the conservation of the site. The bids were 10,20,50,100 and 500 pesos respectively. It was found out that if the respondents have visited the site, the more likely tthey were willing to pay for the conservation. Moreover, bid prices were found negatively signed and significantly determining the WTP of respondent thereby, confirming the law of demand. Respondents' levels of income also affect their willingness to pay in which if they have higher income, they will likely pay. alos, the higher their level of education, the more likely they were concerned and willing to pay for the conservation. Using Hanneman's (1984) formula, the maximum value of Nasadjan Falls per respondent was Php213 per year that means they were willing to pay a maximum amount of Php213 annually for the conservation of the site. This can be translated to Php201, 964.03, which is the social WTP or the social benefits of conservation (conservation value). Added to this, will be estimated recreational value amounting to Php 270, 600, therby strengthening the imperative for the local government unit and other sectors to conserve the Nasadjan Falls. Indeed, Nasadjan Falls has been the potential for ecotourism thus, it is indispensable to conserve and improve the site.